Aproximación a los seres intermedios de la filosofía griega - Rodríguez Moreno, Inmaculada; López Férez, Juan Antonio, 1940- (Madrid: Ediciones Clásicas, 2000)
The field of Greek divinities is very complex owing to the existence of a hierarchy which contains intermediate beings between gods and men. These beings, ȁγγєλοι, demons and heroes, are going to connect the divine world with the human and to acquire, according to the evolution of Greek thought, a special importance in their terminology, figure, gradation and functions. The actual analysis proposes a study of these beings in Greek philosophy, from Presocratic philosophers until imperial period (fith century A. C.).
Keywords: Filosofía griega; Dioses